2007
DOI: 10.1016/j.virol.2007.03.006
|View full text |Cite
|
Sign up to set email alerts
|

AL1-dependent repression of transcription enhances expression of Tomato golden mosaic virus AL2 and AL3

Abstract: Studies using Nicotiana benthamiana protoplasts have determined that repression of upstream transcription by AL1 protein enhances AL2 and AL3 expression in Tomato golden mosaic virus (TGMV). Mutations resulting in the inability of TGMV AL1 protein to associate with its cognate binding site, result in a decrease in both AL2 and AL3 expression. Reduced expression correlates with an increase in transcription from the AL62 start site, and decreased transcription from downstream initiation sites (AL1935 and AL1629)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Previous studies have shown that some geminivirus-encoded proteins could regulate the transcription activity of itself or the other viral genes in plants [30] [32] . To further understand the influences of AYVV-NT-encoded proteins on the activity of AV3 promoter in the prokaryotic system, the promoter activity assays were performed with the co-expression of individual AYVV-NT-encoded proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that some geminivirus-encoded proteins could regulate the transcription activity of itself or the other viral genes in plants [30] [32] . To further understand the influences of AYVV-NT-encoded proteins on the activity of AV3 promoter in the prokaryotic system, the promoter activity assays were performed with the co-expression of individual AYVV-NT-encoded proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The temporal regulation of viral gene expression observed here is consistent with previously reported regulatory mechanisms in geminivirus infections. This concerns the downregulation of Rep (Haley et al, 1992;Sunter et al, 1993) and the resulting enhanced expression of TrAP and REn (Shung & Sunter, 2007). Also, the fact that TrAP transactivates the expression of the CP and NSP genes (Ruiz-Medrano et al, 1999;Sunter & Bisaro, 1991 requires its expression prior to that of CP and NSP.…”
Section: Discussionmentioning
confidence: 99%
“…6b). At some stage, Rep represses its own expression, and the synthesis of the shorter complementary-sense transcript(s) encoding TrAP and REn is maintained at a high level or is even enhanced (Shung & Sunter, 2007). At this stage, MP is also expressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deconstructed virus strategy, in which only those cis ‐ (IR) and trans ‐ (Rep/RepA) elements essential for replication are utilized, have several advantages over the use of full viruses: (1) deleterious effects derived from the action of other viral proteins are avoided; (2) size limitation is less strict than with full viruses; (3) the restrictions imposed by host range may be less stringent – but nevertheless need to be considered (Box 2). Additionally, the expression of Rep/RepA from a promoter other than its own (either constitutive, like the Cauliflower mosaic virus 35S promoter, or inducible) would prevent the Rep‐mediated downregulation of its own expression in late stages of the infection (Shung & Sunter, ), therefore waiving a break in replication and potentially enhancing the accumulation of viral replicons.…”
Section: Geminivirus‐based Replicons: All From One – and One For Allmentioning
confidence: 99%